MANAGEMENT OF PUBLIC TRANSPORTATION PERFORMANCE MODEL BASED ON SAFETY TRANSPORTATION, PERIODIC TRANSPORTATION TEST, BEHAVIOR, AND SATISFACTION IN CIREBON CITY. - Hermawan, Herry (Journal of Green Science and Technology, 2020)
The development of cities in Indonesia is marked by the high number of commuters (commuters) who travel between the main city and the surrounding city or district (hinterland) or between regions within a city due to an increase in population, population activities, types of services, and the relative functioning of the economy national and regional level of a country..       Transportation problems and challenges are multi-dimensional between transportation systems and urban systems, both operational, management and policy aspects. Urban transport policies that care about sustainable development in developing countries are very complex, but can be studied especially in the public transportation system because it is more possible when compared to private transport at this time.       In Indonesia, the number of motorized vehicles is increasing every year. The addition of that number in 2012 reached 10,036 million units, resulting in the population recorded in the Indonesian National Police increased 12% to 94.292 million units compared to only 84.19 million in 2011 (Kurniawan, 2013). Based on data from the National Police also stated that in 2012 there were 109,038 accident cases with 27,441 people died. Different data from the Coordinating Ministry for Economic Affairs and People's Welfare of the Republic of Indonesia states that motorcycle rider accidents have reached 120,226 times or 72% of all traffic accidents in a year. Most accident cases occur in people with lower middle economic level as motorcycle and public transportation users (State Intelligence Agency, 2013).       As released by WHO (World Health Organization), of all accidents that occur on the highway, the human error factor (human error) has the highest contribution, reaching between 80-90 percent compared to the factor of vehicle vehicle improperities ranging from 5-10 percent, as well as due to damage to road infrastructure by 10-20 percent (DG Hubdat, 2010). Vehicle facilities that often occur are less than 1 millimeter of tire grooves resulting in vehicle skid or tire breaks, brakes failing, metal fatigue resulting in broken vehicle parts, worn equipment not replaced, and various other causes. This is very much related to the technology used and the care done to the vehicle. One of the government's efforts to improve road safety is through safety vehicle action programs such as compliance with vehicle operations, organizing periodic and type test repair procedures, handling overloading, vehicle scrapping, and developing motor vehicle design that aims to improve vehicle safety technology (DG Hubdat, 2013).Keywords:Transportation Performance, User Satisfaction.